The All-sky Spectrometer of Hot Cosmic Plasma - Kambarova, Zh.T.; Saulebekov, A.O.; Trubitsyn, A.A. (The Astronomical Journal, 2022)
The main instruments for analyzing the processes occurring in cosmic plasma are energy and mass analyzers of charged particle beams. The analyzers’ operation is based on the separation of charged particles according to the energies of their motion or their masses in electric or magnetic fields. Currently, the top-hat analyzer is considered the main instrument for obtaining information about the state of cosmic plasma. However, it has a number of disadvantages: a significant time cycle for registering angular dependences in a total solid angle of 4π sr and low accuracy of determining the polar angles, which are associated with the need to rotate the analyzer during measurements. Over the past 20 years, plasma analyzers with a large viewing angle have been developed as an alternative to the top-hat analyzer. The design of the analyzer proposed in this work is capable of measuring plasma characteristics in a solid angle of 2π sr in one act of data registration. The all-sky spectrometer of hot cosmic plasma consists of two stages: the first stage is a conical lens of an original design, which serves to transform an extremely wide entrance flow of particles into a narrow cone-shaped beam; the second hexapole-cylindrical stage plays the role of an energy analyzer of a narrow cone-shaped flow. The paper describes the calculations and modeling of the proposed analyzer on the basis of original numerical and approximate analytical methods for designing systems of electron and ion optics. The main parameters of the device are calculated.